Respuesta :

Answer:

540

Step-by-step explanation:

f(x) = x(x - 1)

g(x) = 3x

(f* g)(x) = x(x - 1) 3x

            = (x^2 -x) * 3x

            = 3x^3 -3x^2

            =3x^2(x-1)

Let x = 6

(f* g)(6) = 3*6^2( 6-1)

            =   3*36 *5

                   540        

Answer:

540

Step-by-step explanation:

(f*g)(6)=f(6)*g(6).

Now we need to find f(6) and g(6).  Once we find their values we multiply them.

f(6) means to replace x in x(x-1) with 6:

6(6-1)

6(5)

30

So f(6)=30.

g(6) means to replace x in 3x with 6:

3(6)

18

So g(6)=18.

(f*g)(6)=f(6)*g(6)=30*18=540.

ACCESS MORE